Methods for studying gut parasites and their interaction with the host and the host microbiome - Drozdz, Jessica Anna (Jihočeská univerzita, 2020)
Gastrointestinal issues and diseases have been falsely associated with Blastocystis hominis for decades and was treated mainly with metranidazole. The role of Blastocystis in the human gut is still unclear and has been found more frequently in healthy humans. The main focus of this thesis and study was to test isolation protocols for RNA extraction with the goal of obtaining sufficient Blastocystis data for genomic analyses.
Methods for studying gut parasites and their interaction with the host and the host microbiome
Keywords: Blastocystis hominis; B. hominis; gut microbiome; pathogen; symbiont; commensal; Blastocystis hominis; B. hominis; gut microbiome; pathogen; symbiont; commensal